High hydrogen storage capacity of rice hull based porous carbon - Chen, Haibin; Wang, Haibo; Xue, Zhiping; Yang, Lufeng; Xiao, Yong; Zheng, Mingtao; Lei, Bingfu; Liu, Yingliang; Sun, Lixian (International journal of hydrogen energy, 2012)
A kind of porous carbon with high specific surface area (approximately 4000 m2/g) was prepared from rice hull through carbonization and sodium hydroxide activation. The effects of preparation parameters on the characteristics of the porous carbon were studied. The properties of these porous carbon samples were investigated by X-ray diffraction and scanning electron microscope (SEM) and Fourier transform infrared spectroscopy. The rice hull based porous carbon exhibits high hydrogen storage capacity of 7.7 wt% at 77 K and 1.2 MPa. ► The porous carbon was prepared from rice hull by NaOH activation. ► Its BET surface area achieve to 3969 m2/g. ► Its hydrogen storage reach to 7.7 wt% at 77 K and 1.2 MPa.